Salutogenesis: A new approach toward oral health promotion - Manpreet Kaur; Ritu Jindal; Rohini Dua; Aanchal Gautam; Ramandeep Kaur (Wolters Kluwer Medknow Publications, 2017)
Introduction: Sense of coherence (SOC) is hypothesized to be an important psychological factor that enables people to cope with stressors and successfully maintain and improve health. Very few publications report on the relationship between "salutogenesis," as measured by the concept of SOC and oral health status. However, little is known about the relationship between the mother's SOC and dental caries of their children. Aims and Objectives: The aim of the present study was to explore the impact of mother's SOC level on dental caries status of their children. Materials and Methods: A school-based cross-sectional study was conducted with the children aged 4-8 years attending public school (n = 200). Questionnaires were applied to mothers to obtain level of SOC. Dental caries status in children was assessed using decayed, missing, filled tooth surfaces (DMFS) and/or dmfs index. One-way analysis of variance F-test and post hoc Tukey test were used to assess the effect of mother's SOC level on their children's caries dmfs index. Results: Mean of dmfs and/or DMFS in children showed statistically significant relation with their mother's SOC level (P < 0.01). On intergroup comparison, significant (P < 0.01) difference was found when mean of dmfs and/or DMFS with mothers having low SOC and high SOC was compared. However, there was no significant relation when mean was compared to mothers with medium and low SOC. Conclusion: Dental caries of children gets influenced by mother's SOC level. There was an inverse relationship between mother's SOC level and their children dental caries status.